Effect of Candesartan and Ramipril on Liver Fibrosis in Patients with Chronic Hepatitis C Viral Infection: A Randomized Controlled Prospective Study - Tarek M. Mostafa; Gamal A. El-azab; Gamal A. Badra; Alyaa S. Abdelwahed; Abeer A. Elsayed (Elsevier, 2021)
ABSTRACT: Objective: This study aimed at evaluating the effects of candesartan and ramipril on liver fibrosis in patients with chronic hepatitis C.Methods: This randomized controlled prospective study involved 64 patients with chronic hepatitis C and liver fibrosis. Participants were randomized into 3 groups: group I (control group; n = 21), members of which received traditional therapy only; group 2 (ramipril group; n = 21), members of which received traditional therapy plus 1.25 mg/d oral ramipril; and group 3 (candesartan group; n = 22), members of which received traditional therapy plus 8 mg/d oral candesartan. Patients were assessed at baseline and 6 months after intervention through measuring of liver stiffness (Fibro-Scan; Echosens, Paris, France); evaluation of the serum levels of hyaluronic acid and transforming growth factor beta-1; and calculation of indices of liver fibrosis, including fibrosis index based on the 4 factors and aspartate transaminase-to-platelet-ratio index. Data were analyzed using paired t test and 1-way ANOVA followed by Tukey's honest significant difference test for multiple pairwise comparisons.Results: At baseline, the 3 study groups were statistically similar in demographic and laboratory data. After treatment, the 3 study groups showed significant decrease in liver stiffness, serum levels of hyaluronic acid and transforming growth factor beta-1, and indices of liver fibrosis compared with baseline data (P < 0.001). Six months after treatment, patients taking ramipril and candesartan showed significant improvement in all measured parameters compared with the control group. Additionally, the candesartan-treated group showed significant decrease in liver stiffness, biomarkers, and indices of liver fibrosis compared with ramipril recipients.Conclusions: The administration of ramipril and candesartan in patients with chronic hepatitis C with hepatic fibrosis was well tolerated and effective in improving liver fibrosis. angiotensin II receptor 1 (AT1) antagonist candesartan maintained antifibrotic effects more effectively than ramipril and may represent a safe and effective therapeutic strategy for liver fibrosis in patients with chronic liver diseases. ClinicalTrials.gov identifier: NCT03770936. (Curr Ther Res Clin Exp. 2022; 83:XXX-XXX) © 2022 Elsevier HS Journals, Inc.